The Faithfulness of Jesus Christ in Hippolytus's De Christo et Antichristo: Overlooked Patristic Evidence in the Πίστις Χριστοῦ Debate - Bird, Michael 1974-; Whitenton, Michael R. (2009)
The debate over the meaning of πίστις Χριστοῦ has been continuing for some time and shows no signs of abating, yet one conclusion has remained constant: the Church Fathers, generally, did not understand πίστις Χριστοῦ in the Pauline materials in the subjective sense as the ‘faithfulness of Christ’. Furthermore, there has heretofore been no text that correlates Jesus' faithfulness with his death on the cross in patristic writings. In light of that, the aim of this study is (1) to offer a critique of recent work on πίστις Χριστοῦ in the Church Fathers, and (2) to break the longstanding silence by presenting overlooked evidence from Hippolytus's De Christo et Antichristo that unambiguously relates Jesus' faithfulness to his death on the cross.
Keywords: Apostle Paul; Church Fathers; Hippolytus; Pistis Christou; faithfulness of Christ